Evaluating the Work Efficiency of the Library in the Web Environment - O. M. Udartseva (Библиосфера, 2022)
The article deals with assessing the efficiency of website management (EWM) in order to its development and increase the efficiency of its functioning. The concept “efficiency” in relation to the activities of the library in the web environment is analyzed It was concluded that the efficiency of a library website development can be measured by assessing the dynamics of webometric data, and one can get important information on positive or negative effect of the library website management process. A point-based methodology for assessing EWM has been developed, which makes it possible not only to control the process of managing the library own website, but also allows one the comparison of the evaluation coefficients of the EWM in other libraries, regardless of their type. The obtained coefficient for the evaluation of the EUS library indicates how effectively the website is being developed in the information web space. The proposed methodology is quite flexible and can vary depending on the set of key tools.